The ultraviolet properties of star-forming galaxies - I. HST WFC3 observations of very high redshift galaxies - Wilkins, S; Bunker, A; Stanway, E; Lorenzoni, S; Caruana, J (2011)
The acquisition of deep near-IR imaging with Wide Field Camera 3 on the Hubble Space Telescope has provided the opportunity to study the very high redshift Universe. For galaxies up to z≈ 7.7 sufficient wavelength coverage exists to probe the rest-frame ultraviolet (UV) continuum without contamination from either Lyman α emission or the Lyman α break. In this work we use near-infrared (near-IR) imaging to measure the rest-frame UV continuum colours of galaxies at 4.7 < z < 7.7. We have carefully defined a colour-colour selection to minimize any inherent bias in the measured UV continuum slope for the drop-out samples. For the highest redshift sample (6.7 < z < 7.7), selected as z-band drop-outs, we find mean UV continuum colours approximately equal to zero (AB), consistent with a dust-free, solar metallicity, star-forming population (or a moderately dusty population of low metallicity). At lower redshift we find that the mean UV continuum colours of galaxies (over the same luminosity range) are redder, and that galaxies with higher luminosities are also slightly redder on average. One interpretation of this is that lower redshift and more luminous galaxies are dustier; however, this interpretation is complicated by the effects of the star formation history and metallicity and potentially the initial mass function on the UV continuum colours. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.